DIGITIZATION WORK IN THE STATE ARCHIVES OF KHORESM REGION (TAMADDUN NURI JURNALI, 2025)
This article analyzes the process of strengthening the material and technical base and digitizing archival documents in the Khorezm regional state archives system.